FAKTOR-FAKTOR YANG MEMPENGARUHI KEDISIPLINAN WAKTU PENDISTRIBUSIAN BBM PADA AWAK MOBIL TANGKI DI PT.X - Aprilia Rosa Hafsari; Ida Wahyuni; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Crew Tank Vehicle (CTV) distribute fuel oil based on stations stated in Loading Order and must be based on time target that called by Round Trip Hour (RTH). A job as CTV need high disicipline in time because of the dense schedule delivery fuel oil and in order to achieve the target delivery per day determined by holding company. Some cases founded CTV got Round Trip Hour Over that hinder the company’s productivity. The purpose of this research was to analyze factors that influence the work discipline in the distribution of fuel oil. Independent variable were compensation, firmness leader, sanctions, and supervision. The kind of research was cross sectional study in descriptive analytic. Population in this research was the entire of CTV in PT.X which consisted of 631 people with the sampling method used Lemeshow Formula (d=10%) order to obtained sample minimum as much as 47 people and choosen by incidental sampling technique. This research used an instrumen in the form of questionnaire. The results showed that 50% respondents got a less discipline in work. Statistic analyze which used logistic regression were used for see the influence of compensation, firmness leader, sanctions, and supervision to the discipline of fuel oil distribution. The results showed that there was no influence of compensation (p=0,540) and firmess leader (p=0,876) to work discipline. And there was an influence of sanctions (p=0,013) and supervision (p= 0,007) to the discipline of fuel distribution in PT.X. It was suggested to Company for check on a tank truck routinely before it left, review fatigue of worker, and maximize the supervision through GPS system function.